(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the tasks of a social worker in situations related to the processes of education of young people today, problems arising from contact with society and situations related to their families, or the activities of a social worker in public institutions. It was also thought about ensuring the educational rights of citizens in need of social assistance, promoting the manifestation of the talent of Highly Gifted Youth and conducting social work practices in modern education for their support (on the example of the Russian Federation).